Conflict and Controversy in Small Cinemas - Falkowska, Janina; Loska, Krzysztof (Interdisciplinary Studies in Performance, 2018)
This book examines small cinemas and their presentation of society in times of crisis and conflict from an interdisciplinary and intercultural point of view. The authors concentrate on economic, social and political challenges and point to new phenomena which have been exposed by film directors. They present essays on, among others, Basque cinema; gendered controversies in post-communist small cinemas in Slovakia and Czech Republic; ethnic stereotypes in the works of Polish filmmakers; stereotypical representation of women in Japanese avant-garde; post-communist political myths in Hungary; the separatist movements of Catalonia; people in diasporas and during migrations. In view of these timely topics, the book touches on the most serious social and political problems. The films discussed provide an excellent platform for enhancing debates on politics, gender, migration and new aesthetics in cinema at departments of history, sociology, literature and film.